Microglia modulate hippocampal synaptic transmission and sleep duration along the light/dark cycle. Issue 1 (6th September 2021) - Corsi, Giorgio; Picard, Katherine; di Castro, Maria Amalia; Garofalo, Stefano; Tucci, Federico; Chece, Giuseppina; del Percio, Claudio; Golia, Maria Teresa; Raspa, Marcello; Scavizzi, Ferdinando; Decoeur, Fanny; Lauro, Clotilde; et al.
Abstract: Microglia, the brain's resident macrophages, actively contribute to the homeostasis of cerebral parenchyma by sensing neuronal activity and supporting synaptic remodeling and plasticity. While several studies demonstrated different roles for astrocytes in sleep, the contribution of microglia in the regulation of sleep/wake cycle and in the modulation of synaptic activity in the different day phases has not been deeply investigated. Using light as a zeitgeber cue, we studied the effects of microglial depletion with the colony stimulating factor‐1 receptor antagonist PLX5622 on the sleep/wake cycle and on hippocampal synaptic transmission in male mice. Our data demonstrate that almost complete microglial depletion increases the duration of NREM sleep and reduces the hippocampal excitatory neurotransmission. The fractalkine receptor CX3CR1 plays a relevant role in these effects, because cx3cr1 GFP/GFP mice recapitulate what found in PLX5622‐treated mice. Furthermore, during the light phase, microglia express lower levels of cx3cr1 and a reduction of cx3cr1 expression is also observed when cultured microglial cells are stimulated by ATP, a purinergic molecule released during sleep. Our findings suggest that microglia participate in the regulation of sleep, adapting their cx3cr1 expression in response to the light/dark phase, and modulating synaptic activity in a phase‐dependent manner. Main Points: Neuronal spontaneous activity and microglial CX3CR1 increase in the dark. Microglia alterations affect sleep and synaptic transmission in a phase‐dependent manner. CX3CR1 mediates microglial effects on neuronal activity in the light/dark cycle.